Reduced Regional NREM Sleep Slow-Wave Activity Is Associated With Cognitive Impairment in Parkinson Disease - Schreiner, Simon J.; Imbach, Lukas L.; Valko, Philipp O.; Maric, Angelina; Maqkaj, Rina; Werth, Esther; Baumann, Christian R.; Baumann-Vogel, Heide (Frontiers in Neurology, 2021)
Growing evidence implicates a distinct role of disturbed slow-wave sleep in neurodegenerative diseases. Reduced non-rapid eye movement (NREM) sleep slow-wave activity (SWA), a marker of slow-wave sleep intensity, has been linked with age-related cognitive impairment and Alzheimer disease pathology. However, it remains debated if SWA is associated with cognition in Parkinson disease (PD). Here, we investigated the relationship of regional SWA with cognitive performance in PD. In the present study, 140 non-demented PD patients underwent polysomnography and were administered the Montréal Cognitive Assessment (MoCA) to screen for cognitive impairment. We performed spectral analysis of frontal, central, and occipital sleep electroencephalography (EEG) derivations to measure SWA, and spectral power in other frequency bands, which we compared to cognition using linear mixed models. We found that worse MoCA performance was associated with reduced 1-4 Hz SWA in a region-dependent manner (F 1,687 =11.67, p<0.001). This effect was driven by a reduction of regional SWA in the lower delta frequencies, with a strong association of worse MoCA performance with reduced 1-2 Hz SWA (F 2,687 =18.0, p<0.001). The association of MoCA with 1-2 Hz SWA followed an antero-posterior gradient, with strongest, weaker, and absent associations over frontal (rho=0.33, p<0.001), central (rho=0.28, p<0.001), and occipital derivations, respectively. Our study shows that cognitive impairment in PD is associated with reduced NREM sleep SWA, with regional and frequency-specific predominance in lower delta frequencies (1-2 Hz) and over frontal regions. This finding suggests a potential role of reduced frontal slow-wave sleep intensity in cognitive impairment in PD.